2016
DOI: 10.1097/md.0000000000004175
|View full text |Cite
|
Sign up to set email alerts
|

Hyperaldosteronism and cardiovascular risk in patients with autosomal dominant polycystic kidney disease

Abstract: Hypertension is commonly associated with autosomal dominant polycystic kidney disease (ADPKD), often discovered before the onset of renal failure, albeit the pathogenetic mechanisms are not well elucidated. Hyperaldosteronism in ADPKD may contribute to the development of insulin resistance and endothelial dysfunction, and progression of cardiorenal disease. The aim of study was to evaluate the prevalence of primary aldosteronism (PA) in ADPKD patients and identify some surrogate biomarkers of cardiovascular ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Several lines of evidence, suggest a hyperactivation of renin-angiotensin-aldosterone system (RAAS), with ectopic production of renin, angiotensinogen , angiotensin-converting enzyme and angiotensin II by cystic epithelium [2, 12]. Angiotensin II seems to represent the main stimulus for the production of aldosterone, and the presence of hyperaldosteronism in ADPKD, could contribute to the development of insulin resistance and endothelial dysfunction, with impaired nitric oxide-related vasorelaxation, and progression of cardiorenal disease [15]. Recently, some authors showed an essential role of the cilia in proper development of the vascular system [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence, suggest a hyperactivation of renin-angiotensin-aldosterone system (RAAS), with ectopic production of renin, angiotensinogen , angiotensin-converting enzyme and angiotensin II by cystic epithelium [2, 12]. Angiotensin II seems to represent the main stimulus for the production of aldosterone, and the presence of hyperaldosteronism in ADPKD, could contribute to the development of insulin resistance and endothelial dysfunction, with impaired nitric oxide-related vasorelaxation, and progression of cardiorenal disease [15]. Recently, some authors showed an essential role of the cilia in proper development of the vascular system [16].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in PC1 and PC2, transmembranes glicoproteins that are colocalized to the primary cilium of the kidney tubular epithelial cells, cause lower intracellular levels of calcium and increased intracellular cyclic adenosine monophosphate, with aberrant cell proliferation and fluid secretion into cysts [11-13]. ADPKD is a systemic disease, that may involve different organs, showing a high phenotypic variability [14-15], and cardiovascular complications are the major cause of morbidity and mortality, with a cardiac-related death that is estimated to be 1.6- to 3.2-fold higher in these patients than in the general population [16-17]. Currently, there are no prognostic tools to identify ADPKD patients with high cardiovascular risk.…”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of aldosterone and angiotensin II could lead to systemic fibrosis, mitogenesis and stimulate the formation of cysts . Many studies support the evidence of the aldosterone role in determining cardiovascular damage, regardless of angiotensin II and blood pressure . Indeed the hormone could have a fibrotic effect on vascular smooth muscle cells, endothelial cells, cardiomyocytes and renal tissue .…”
Section: Discussionmentioning
confidence: 98%
“…6 Many studies support the evidence of the aldosterone role in determining cardiovascular damage, regardless of angiotensin II and blood pressure. 5,6,12 Indeed the hormone could have a fibrotic effect on vascular smooth muscle cells, endothelial cells, cardiomyocytes and renal tissue. 24 Our results showed that TFV, was correlated positively also with insulin values, ABI index and LVMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation